2019
DOI: 10.1111/pre.12412
|View full text |Cite
|
Sign up to set email alerts
|

Coelastrella astaxanthina sp. nov. (Sphaeropleales, Chlorophyceae), a novel microalga isolated from an asphalt surface in midsummer in Japan

Abstract: SUMMARY We taxonomically examined an algal strain (Ki‐4) isolated from a dry asphalt surface in mid‐summer of 2003. The vegetative cells were solitary, covered by a cell wall ornamented with meridional ribs, and contained hollow spherical chloroplasts and a pyrenoid. The cells exhibited a high tolerance to unfavorable photo‐oxidative stress conditions, and in culture developed a reddish coloration due to the accumulation of a water‐soluble astaxanthin‐binding protein, which was identified as a novel protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…A similar cell wall surface has been registered by SEM for different Coelastrella species around the world, i.e. C. astaxanthina (Kawasaki et al 2019 ), C. ellipsoidea and C. multistriata var. grandicosta (Gopalakrishnan et al 2014 ); C. terrestris (PunČochářová and Kalina 1981 ; Gärtner and Ingolić 1993 ; Tschaikner et al 2007a , b ; Kaufnerová and Eliáš 2013 ; Xiao et al 2017 ); C. aeroterrestrica (Uzunov et al 2008 ); C. oocystiformis (PunČochářová and Kalina 1981 ), C. rubescens (PunČochářová and Kalina 1981 ; Kaufnerová and Eliáš 2013 ); C. saipanensis strain FACHB-2138 (Wang et al 2019a ), C. thermophila (Wang et al 2019b ), C. vacuolata (Hanagata 2001 ); C. multistriata var.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A similar cell wall surface has been registered by SEM for different Coelastrella species around the world, i.e. C. astaxanthina (Kawasaki et al 2019 ), C. ellipsoidea and C. multistriata var. grandicosta (Gopalakrishnan et al 2014 ); C. terrestris (PunČochářová and Kalina 1981 ; Gärtner and Ingolić 1993 ; Tschaikner et al 2007a , b ; Kaufnerová and Eliáš 2013 ; Xiao et al 2017 ); C. aeroterrestrica (Uzunov et al 2008 ); C. oocystiformis (PunČochářová and Kalina 1981 ), C. rubescens (PunČochářová and Kalina 1981 ; Kaufnerová and Eliáš 2013 ); C. saipanensis strain FACHB-2138 (Wang et al 2019a ), C. thermophila (Wang et al 2019b ), C. vacuolata (Hanagata 2001 ); C. multistriata var.…”
Section: Discussionsupporting
confidence: 60%
“…have been neglected in local environmental studies (in Norway and elsewhere). Only the last year, four new species and two new varieties have been described of Coelastrella (Kawasaki et al 2019 ; Wang et al 2019b ). In Norway, there are few observations of other related green coccoid microalgae, including Dimorphococcus and Coelastrum (also members of the Coelastroideae), and Chlorococcum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Okinawa-4N (Oki-4N), a eukaryotic microalgal strain isolated from a pond in 2002, was found to produce large amounts of aqueous pigments under photooxidative stress conditions, which was similar to that of Coelastrella astaxanthina Ki-4 23,24 . The 18S rRNA gene and internal transcribed spacer 2 (ITS2) gene sequences revealed that Oki-4N belongs to the family Scenedesmaceae of the order Chlorococcales and was placed in the Scenedesmus sensu stricto clade 24,25 , which includes the type species of the genus Scenedesmus, Scenedesmus obtusus Meyen 26,27 . Based on genotypical and morphological characterization (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The composition of the A3 medium was the same as previously described 23 . The 18S rRNA gene and ITS2 sequence were analysed as previously described 23,24 . Briefly, the 18SF1 (5′-TAATGATCCTTCCGCAGGTT-3′) and 18SR1 (5′-CCTGGTTGATCCTGCCAG-3′) primers were used to amplify and sequence the 18S rDNA fragments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation